Improving Governance and Inclusion Public Services in Selaparang District Mataram City - Sutarna, Iwan Tanjung; Hakim, Adhar; Hendriadi, Hendriadi (Universitas Pancasakti, 2025)
This article aims to analyze Selaparang Inclusion as a strategic approach to strengthening governance and improving the quality of public services in Selaparang District, Mataram City. This study uses a qualitative descriptive method assisted by the NVivo 12 Plus tool to analyze the data. The results show that the active participation of local stakeholders, such as the Selaparang District Head and the Mataram Inclusive Formulation Team, indicates a collaborative and reflective process, although obstacles are still encountered in directing the concept of inclusion so that it is easily understood by the wider community. Meanwhile, the main targets of Selaparang Inclusion show that the elderly are the group with the greatest attention (30%), followed by people with disabilities (23.33%), children (20%), women (16.67%), and indigenous communities (10%). These findings provide a concrete picture of the direction of priority programs and indicate the still low attention to women and indigenous communities. Overall, the Selaparang Inclusion program has succeeded in becoming a collaborative platform across actors in building an inclusive region. However, further efforts are still needed to increase representation and access to services for underrepresented groups. This program is an example of good practice in realizing just, equal, and participatory governance at the local level.